The Influence Of Sales Promotion And Customer Experience On Purchase Intention Mediated By Customer Satisfaction - Lidya Grace; Ratlan Pardede (Ridwan Institute, 2023)
The fast-moving consumer goods (FMCG) retail business in Indonesia has been experiencing rapid growth since 2019. With over 3.6 million traditional retailers (warungs), the Indonesian economy has greatly benefited from this industry, with a business potential of up to US 58 billions (Maulana, 2022). As digital transformation continues, business owners are increasingly digitizing their operations. The B2B e-commerce model is used to simplify the procurement process for shop owners. The purpose of the research is to examine the impact of Sales Promotions and Customer Experience on Purchase Intention mediated by Customer Satisfaction among AKSESMU digital application users in JABODETABEK. In addition, this research aims to identify the variables that directly or indirectly influence purchase Intention. Data was collected through an online survey using Google Forms from 207 respondents of AKSESMU digital application users in JABODETABEK. The collected data was analyzed using AMOS software version 24. The results indicate that Customer Experience and Customer Satisfaction have a significant and positive impact on the Purchase Intention of AKSESMU digital application in JABODETABEK.